Barriers to EMS assimilation in the US, Australia, Hong Kong, Norway and Switzerland: A Cross regional comparison - Pervan, Graham; Bajwa, D.; Lewis, L.; King, V.; Muntvold, B.; Schwabe, G. (University of Vienna, 2005)
Electronic Meeting Systems (EMS) have the capabilities to support group members in task collaboration. While there have been many case studies and lab experiments on how EMS can support group tasks, large scale macro investigations exploring EMS adoption and use have been practically non-existent. Furthermore, while several EMS assimilation barriers have been suggested, their validation across organizations remains unexplored. In this paper, we describe a global initiative to explore information technology support for task-oriented collaboration in the US, Australia, Hong Kong, Norway and Switzerland. We focus specifically on EMS and investigate their adoption, use and assimilation barriers in organizations across the five regions. Our results suggest that EMS adoption and use is limited across all the regions. A further investigation in EMS assimilation barriers suggests that these barriers differ across the regions and there is little agreement over how they are ranked. Implications of our findings are discussed for practitioners and researchers.